THE LOWER APTIAN OF THE MANGYSHLAK MOUNTAINS - Boedanova T.N. (My University, 1999)
In the Mangyshlak Mountains, the lower Aptian deposits are represented by thin beds (0.5-1.5 m) of sandstone and conglomerate, and in the Kugusem anticline, this time range spans two conglomerate beds incorporating an intermediate clay member (up to 15 m thick). The lower Aptian beds rest with a hiatus on different horizons of the Cretaceous (Berriasian-Barremian), or on the Middle Jurassic rocks. The beds yielded diverse assemblages of various faunal groups: ammonites, belemnites, bivalves, brachiopods, Echinoidea, and others. The beds represent a condensed sedimentary sequence of the shallow-shelf type and are divisible into the lower Aptian Deshayesites weissi, Deshayesites deshayesi, and Dufrenoya furcata ammonite zones. The lower Aptian ammonite assemblages include 21 species from genera Deshayesites, Dufrenoya, and Cheloniceras, two of which (Deshayesites semenovi and Cheloniceras sinzowi) are new and described in the paper. The paper also presents images of 16 other species, including 11 forms discovered for the first time in the Mangyshlak Mountains.
Keywords: Aptian; Mesozoic::Cretaceous::Lower::Aptian; Мезозой::Меловая::Нижний::Аптский